PWE-132 Therapeutic outcomes following endotherapy for refractory gastroparesis. (8th June 2018) - Gupta, Abhinav; Everson, Martin; Haidry, Rehan; Banks, Matthew; Bown, Stephen; Graham, David; Patel, Kalp; Qarage, Layth; Mari, Amir; Zarate-Lopez, Natalia; LovatSweis, LaurenceRami
Abstract : Introduction: The relative merits of endotherapy for refractory gastroparesis remain unclear. We assessed the symptomatic response of patients undergoing non-surgical pyloric intervention at a specialist tertiary centre. Methods: 57 patients (21 male, mean age 47, 16–81) with medical refractory gastroparesis (29 idiopathic, 5 diabetic, 23 post-gastric transposition) underwent 117 endoscopic treatments from Sep 2013-Sep 2017: either 100IU units of Botox injected into 4 quadrants of the pylorus (n≥66), balloon dilatation to 15–20 mm (EBD, n≥13) or combination therapy (n≥38). Patients with gastric malignancy, pyloric surgery or no follow-up were excluded. Symptoms were assessed immediately prior to each procedure and at first follow up using a retrospective scoring system based on the presence (1 point) or absence (0 points) of Vomiting, Nausea, Bloating or Early satiety. This formulated a composite symptom score (SS) out of 4; positive response was defined by improvement in SS of at least 1. Statistical analysis was performed using Wilcoxon Signed-Rank Test and Fischer's Test. Results: There were no immediate or late complications. Mean symptom score (SS) improved per-patient from 2.1 points at baseline to 1.2 post initial endotherapy(p<0.01) at median follow up of 2.1 months. 20 patients required further endotherapy (median 2.5 treatments; range 2–12); mean SS was 1.0 at latest follow-up. Per-procedure, mean reduction in SS was 0.8 points (p<0.01) with overall positive response rate of 67%. By symptom, vomiting was most responsive to endotherapy (86% pre v 32% post). By treatment type, Botox alone (n≥66) had the highest overall response (78%) compared to EBD (38%, p≥0.02) or combination therapy (66%, p≥0.3). Response to Botox was greater in patients under 40 (83% v 61%, p≥0.04) and females (81% v 33%, p≥0.002). By indication, diabetic GP(n≥17) were most likely to respond (76%). Sub-group analysis showed procedures for gastroparesis (diabetic/idiopathic, n≥75) responded significantly more to Botox (mean SS reduction 1, p<0.01) than EBD (mean SS reduction 0.2, p>0.1) or combination therapy (mean SS reduction 0.44, p≥0.12). Procedures for gastric transposition(n≥42) showed significant SS reduction post combination therapy (2.1 v 1.2, p≥0.01) but not post EBD (1.9 v 1.6, p>0.1) or Botox (1.7 v 1.1, p≥0.08). Conclusions: Endotherapy is a safe and effective treatment for refractory gastroparesis. We found Botox monotherapy significantly improved symptoms in diabetic or idiopathic gastroparesis, especially younger females; conversely, combination therapy was preferable for delayed gastric emptying post gastric transposition. Careful patient selection may augment therapeutic response.